Argentine Left Parties and the 1967 Six-Day War through the Prism of Global Networks and South-South Connections - Jozami, Maximiliano (Anuario de Historia de América Latina, 2019)
The June 1967 war between Israel and the armies of Egypt, Syria and Jordan had an important impact on the Argentine left, which sided with the Arab countries. The Communist Party of Argentina (PCA), which had a significant influence on the Jewish community, defended the policy of the Soviet Union, while Política Obrera (PO) and the Revolutionary Workers’ Party (PRT), two Trotskyist currents, were critical of the Soviet policy and saw in the political process of the Middle East an ongoing national revolution that could develop into a socialist revolution. Even though the three parties openly repudiated anti-Semitism and denounced the calls to expel the Jewish population from Israel/Palestine, they were not exempt of the use of anti-Semitic (and Orientalist) tropes. They described Israel as a mere ‘pawn of US Imperialism’ devoid of agency and, with the exception of the PCA, ignored the existence of the Palestinians as a distinct national group. The debate of the Israel/Palestine question at the Tricontinental Conference held in Havana in 1966 influenced the left as a whole, and seems to have informed the positions of PO, organization that became the first Marxist party in the world to have called for the political destruction of the State of Israel, which was to have been carried out by the revolutionary alliance of the Arab and Jewish masses of the Middle East. Both the PCA and PRT defended Israel’s right to exist instead.
Keywords: Israel, Palestine, Tricontinental, Communism, Trotskyism, Anti-Zionism